(3fOGAGJ GdefGf dCgd GdEjeGf (B/s - (3GdSYOj, YHO GdQMef Hf fGUQ Hf YHO Gddg,s 1307-1376 (3gLQjs; (3GdCMeO, eMeO Hf QjGVs ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2005)
(3jTJed gPG GdcJGH Ydi fOGAGJ cKjQI ef Gddg JYGdi Edi YHGOg GdeDefjf aj GdYOjO ef GdCehQ GdJj JNUge(B.s
Keywords: (3GdEjeGf (B((3ESdGe(B)s; (3hYX hEQTGOs